Comparison of Intra- and Extramedullary Implants in Treatment of Unstable Intertrochanteric Fractures - Duymus, Tahir Mutlu; Aydogmus, Suavi; Ulusoy, İbrahim; Kececi, Tolga; Adiyeke, Levent; Dernek, Bahar; Mutlu, Serhat (Elsevier B.V., 2019)
Introduction: Comparison was made of the clinical and radiological results of the surgical treatments of proximal femoral nail (PFN), dynamic hip screw (DHS) or proximal femoral locking compression plate (PF-LCP) in patients with AO 31A2.2/2.3 unstable intertrochanteric femoral fracture(ITF). Methods: Evaluation was made of a total of 91 patients in respect of age, gender, time from fracture to surgery, operating time, amount of blood replacement, total hospitalisation, follow-up period, time to full weight-bearing, time to union, complications and Harris hip scores(HHS). Results: A statistically significant difference was determined between the groups in respect of perioperative operating time, blood replacement and hospitalisation period with the values of the PFN group seen to be superior to those of the other two groups (p < 0.001). No significant difference was determined beween the DHS and PFN groups in respect of time to union and in the long-term HHS, both groups were seen to be superior to the PF-LCP group (p < 0.001). Full weight-bearing was statistically significantly earlier in the PFN group (p < 0.001). The numbers of implant failures was statistically significantly higher in the PF-LCP group (p < 0.001). Conclusion: The new generation intra-medullar nails are easy to apply and have more successful clinical results compared to extra-medullar implants in the treatment of A2 unstable ITF. Due to the high rates of implant failure, PF-LCP should not be preferred in these fractures. © 2018
Keywords: Dynamic hip screw; Proximal femoral nail; Proximal femur locking compression plate; Unstable intertrochanteric fracture